Self efficacy, physical work environment and job satisfaction - Boby Handoko; Rini Sarianti (Universitas Negeri Padang, 2021)
The aim of this research is to know and analyze the influence of self efficacy and physical work environment on employee satisfaction in Sejati Swalayan Pasaman Barat. This research belongs to the type of causative descriptive research. The population in this study were all employer in Sejati Swalayan, Pasaman Barat. The sampling technique in this study used a total sampling technique which amounted to 36 people. The analysis technique used is SPSS. The outcomes of this investigation are: (1) Self-efficacy take effect an absolute to job satisfaction in employees of Sejati Swalayan Pasaman Barat. (2) Physical Work Environment take effect positive effect to job satisfaction on employees of Sejati Swalayan Pasaman Barat.